A Literature Review on Remedial Reading Teachers: The Gaps in the Philippine Context - Bautista, Judy C.; Gatcho, Al Ryanne G. (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
Remedial reading teachers are forerunners in elevating the reading achievement of students in schools. In the Philippines, there has been a continual enrichment of the reading skills of struggling readers through the initiatives of remedial reading teachers. However, the country does not have clear policies on the identities, roles, challenges, and needs of such teachers. This paper presents a review of the literature on remedial reading teachers. The results revealed that remedial reading teachers performed various roles in schools and that the cultivation of the roles and duties of remedial reading teachers rely so much on different factors, some of which are knowledge and the skills that they have, philosophical views in education and the whole school community, the rapport that remedial reading teachers have with their colleagues, the support of the administrators to their personal and career developments, and provisions of the local government. It was also evident in the review that literature and studies are scarce regarding remedial reading teachers in the Philippines, thus, suggesting to explore on the what's and the how's of remedial reading teachers in a hope of creating clear policies that will strengthen their identities and support their professional developments.